Production of cast iron during the melting of mineral raw materials in coke cupolas - S. L. Rovin; L. E. Rovin; V. A. Jaranov (Литьë и металлургия, 2021)
In the production of mineral raw materials in cupolas, as a by-product and harmful product, a significant amount of cast iron (up to 3 % of the raw material) is formed and, as a rule, thrown into the dumps. The article presents technical solutions that ensure the separation of mineral melt and cast iron. In addition, the article describes the results of optimizing the design of ladders used for draining liquid metal from the mineral wool cupola and transporting it. The resulting cast iron ingots can then be used as a charge in the smelting of branded cast alloys.